Bird-Related Disruption in E.ON's Power Grid - Nilén,Lisa (Master's Theses in Mathematical Sciences, 2026)
Bird collisions with overhead power lines can cause power outages and raise ecological concerns. This thesis analyses bird-related power disruptions in E.ON Energidistribution AB’s Swedish power grid during the period 2009–2025. The aims are to analyse the impact of bird-related outages relative to other causes and to evaluate whether bird diverters reduce such disruptions. The study is based on documented outage data combined with geographical information on grid infrastructure and bird diverter installations. Exploratory data analysis reveals that bird-related outages constitute less than one per cent of all disruptions but shows clear temporal and spatial patterns. Outages are strongly seasonal, with higher frequencies during summer and early autumn, and are more common in coastal regions. Regression modelling using generalised linear models shows a significant long-term decline in bird-related outages, with a negative binomial model providing the best fit due to overdispersion. Survival and competing risks analyses indicate that the risk of bird-related outages is low compared with other causes. The analysis of bird diverters shows a reduction in bird-related outage rates after installation. However, similar reductions are observed in grid sections without diverters, preventing a definitive conclusion regarding their effectiveness.